Phytochemical Screening and Antibacterial Activity of Ethyl Acetate, n-Hexane, and Aqueous Fractions of White Teak (Tectona grandis Linn. f.) Leaves against Escherichia coli - herman herman; Ferdinta Daniasta Setyawan; Anis Akhwan Dhafin; Fendy Prasetyawan (LPPM Akafarma Sunan Giri Ponorogo, 2025)
This study aims to conduct a phytochemical screening and evaluate the antibacterial activity of ethyl acetate, n-hexane, and aqueous fractions of white teak (Tectona grandis Linn f.) leaves against Escherichia coli bacteria. Phytochemical screening was performed to identify active compounds with potential antibacterial properties, such as flavonoids, tannins, saponins, alkaloids, and terpenoids. The antibacterial activity was tested using the disk diffusion and broth dilution methods to determine the inhibition zone, Minimum Inhibitory Concentration (MIC), and Minimum Bactericidal Concentration (MBC). The diffusion test results showed that ethanol extract (11.3 ± 1.02 mm) and the ethyl acetate fraction (18.1 ± 2.46 mm) exhibited significant antibacterial activity, whereas the n-hexane and aqueous fractions did not show any inhibition zones. Statistical analysis using ANOVA indicated a significant difference in antibacterial activity among the treatment groups (F = 163.29; p < 0.05). The broth dilution test revealed that the ethyl acetate fraction had an MIC at a concentration of 12.5%, with an MBC at 25%.